2009
DOI: 10.3892/or_00000401
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumor effect of cimetidine via inhibiting angiogenesis factors in N-butyl-N-(4-hydroxybutyl) nitrosamine-induced mouse and rat bladder carcinogenesis

Abstract: Abstract. The aim of this study was to assess the anti-tumor effect and mechanisms of cimetidine in N-butyl-N-(4-hydroxybutyl) nitrosamine (BBN)-induced bladder carcinogenesis model. Sixty-three male BALB/c mice and 67 male Wister rats were treated with BBN and cimetidine to examine the anti-tumor effect of cimetidine. Immunohistochemistry (IHC) of vascular endothelial growth factor (VEGF), plateletderived endothelial growth factor (PDECGF), and E-selectin were examined to compare their expression in the tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The animal model of bladder cancer induction by BBN have been used in many studies [29][30][31][32][33] mainly because BBN induced alterations in the bladder of rodents that are correspondent to histopathological and molecular features of human transitional cell carcinoma [34][35][36]. In this work, bladder cancer was induced by the addition of 0.05 % of BBN in the drinking water for 4,8,12,18, and 24 weeks with a respective control group for each induction time.…”
Section: Bladder Cancer Inductionmentioning
confidence: 99%
“…The animal model of bladder cancer induction by BBN have been used in many studies [29][30][31][32][33] mainly because BBN induced alterations in the bladder of rodents that are correspondent to histopathological and molecular features of human transitional cell carcinoma [34][35][36]. In this work, bladder cancer was induced by the addition of 0.05 % of BBN in the drinking water for 4,8,12,18, and 24 weeks with a respective control group for each induction time.…”
Section: Bladder Cancer Inductionmentioning
confidence: 99%
“…The antitumor effect of cimetidine has been suggested to involve various mechanisms underlying its beneficial effects in patients with cancer. In addition to its immunomodulatory effects, cimetidine exerts antitumor activity by inhibiting cancer cell proliferation by blocking histamine receptors [ 24 ], affecting histamine metabolism [ 25 ], blocking the expression of E-selectin to inhibit cancer cell adhesion and prevent metastasis [ 26 ], and inhibiting angiogenesis [ 27 , 28 ]. In our results, cimetidine had mild antitumor activity, but significantly attenuated the antitumor effect of anti-PD-L1 without major toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Additional study of CRC reported that histamine significantly augmented cell proliferation and VEGF production via a COX-2 cascade, and administration of cimetidine notably inhibited this effect [180]. Cimetidine also revealed antitumor activity via inhibiting several angiogenesis factors such as VEGF and platelet-derived endothelial growth factor in chemically-induced bladder carcinogenesis in mice and rats [181]. The potential action mechanisms underlying the antitumor effects of cimetidine are illustrated in Figure 3.…”
Section: Histamine H2 Receptormentioning
confidence: 98%